2001
DOI: 10.1093/pcp/pce117
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Chlorophyll Protein in Brassicaceae Plants is a Stress-Induced Chlorophyll-Binding Protein

Abstract: ;Two kinds of water-soluble chlorophyll (Chl) proteins (WSCPs) have been found, e.g., a WSCP from Chenopodium, Atriplex, Polygonum, and Amaranthus species (class I) and that from Brassica, Raphanus, and Lepidium species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 37 publications
5
102
0
Order By: Relevance
“…Presumably, the chlorophyll precursor chlorophyllide formed during greening bound to WSCP and triggered the dissociation of the RD21::WSCP complex (16). As shown previously, WSCP contains a pigment binding site distantly related to that of the major light-harvesting protein of photosystem II (LHCII) (22) that presumably mediated this effect. Other studies have shown that WSCPs form tetrameric complexes in the presence of chlorophyllide, and thereby shield the pigment against the interaction with molecular oxygen, providing a unique photoprotection mechanism (24).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Presumably, the chlorophyll precursor chlorophyllide formed during greening bound to WSCP and triggered the dissociation of the RD21::WSCP complex (16). As shown previously, WSCP contains a pigment binding site distantly related to that of the major light-harvesting protein of photosystem II (LHCII) (22) that presumably mediated this effect. Other studies have shown that WSCPs form tetrameric complexes in the presence of chlorophyllide, and thereby shield the pigment against the interaction with molecular oxygen, providing a unique photoprotection mechanism (24).…”
mentioning
confidence: 69%
“…The second PI thus far known to inhibit RD21 activity is a protein originally identified as water-soluble chlorophyll-binding protein (WSCP) in Lepidium virginicum and other Brassicaceae, including Arabidopsis (16,17,22,23). This protein contains a Kunitz-type PI signature and, in fact, interacts with RD21 in a tissue-specific manner (16,17,23).…”
mentioning
confidence: 99%
“…In addition to the photosynthesis-related proteins, non-photosynthetic water-soluble chlorophyll (Chl)-binding proteins (WSCPs) have also been found in plants of the Chenopodiaceae, Amaranthaceae, Polygonaceae, and Brassicaceae families. 1) WSCPs can be categorized into two classes; Class I (photoconvertible) and Class II (non-photoconvertible). 1) Class I WSCPs have been found in plant species of the Chenopodiaceae, Amaranthaceae, and Polygonaceae families.…”
mentioning
confidence: 99%
“…1) WSCPs are known to be heat-resistant proteins. 2−4) Based on their photoconvertibility, WSCPs can be categorized into two classes, Class I (photoconvertible type) and Class II (non-photoconvertible type).…”
mentioning
confidence: 99%
“…2−4) Based on their photoconvertibility, WSCPs can be categorized into two classes, Class I (photoconvertible type) and Class II (non-photoconvertible type). 1) Sequence analyses revealed that Chenopodium album WSCP (CaWSCP), a Class I WSCP, is a member of the domain unknown function 538 superfamily 5,6) while all Class II WSCPs belong to the Kunitz-type trypsin inhibitor family. 1,3,7−10) There have been various studies on the biochemical and physicochemical properties of Class I WSCPs, including CaWSCP.…”
mentioning
confidence: 99%